The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/medu.14468
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of medical student reflections on the implicit association test

Abstract: Introduction Health professions educators use the Implicit Association Test (IAT) to raise awareness of implicit bias in learners, often engendering strong emotional reactions. Once an emotional reaction ensues, the gap between learner reaction and strategy identification remains relatively underexplored. To better understand how learners may identify bias mitigation strategies, the authors explored perspectives of medical students during the clinical portion of their training to the experience of taking the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…To understand the experiences of students in this program, we used qualitative analysis on students’ written reflections. Reflection is widely applied in qualitative studies [ 23 , 24 ]. The academic literature on reflection has revealed that it can help us understand participants' internal dialogues and analyze their thought processes.…”
Section: Methodsmentioning
confidence: 99%
“…To understand the experiences of students in this program, we used qualitative analysis on students’ written reflections. Reflection is widely applied in qualitative studies [ 23 , 24 ]. The academic literature on reflection has revealed that it can help us understand participants' internal dialogues and analyze their thought processes.…”
Section: Methodsmentioning
confidence: 99%
“…Despite having had at least two instructional sessions on implicit bias, being not only aware but accepting of their implicit biases, they could not identify strategies to manage the potential impact of their implicit biases. 54 Given these limitations, we propose sustainable longitudinal skill development that harnesses the good intentions of most physicians. Interventions targeting implicit bias must go beyond awareness to providing instruction on strategies for bias management and opportunities for skill development and practice.…”
Section: Limitations Of Common Approaches To Teaching About Implicit ...mentioning
confidence: 99%
“…The IAT and other measures ( 32 ) of implicit bias, stigma, and attitudes toward groups of persons were used among subjects to ( a ) demonstrate the existence of participant implicit biases, ( b ) act as a springboard to create cognitive dissonance for oral and/or written reflection and to practice bias management skills, and ( c ) evaluate interventions. Gonzalez et al ( 37 ) found that using the IAT without priming on its results and without a follow-up debriefing led some subjects (22%) to question the validity of the measure and the existence of implicit biases, and therefore advised judicious use of the IAT and trained facilitators. Subjects who accepted the results of the IAT were not able to develop management strategies for those biases without dedicated instruction.…”
Section: Novel Intervention Contentmentioning
confidence: 99%